The Development of Interpersonal Intelligence in Islamic Boarding School Darul Huda Ponorogo - Nurul Azizah; Silmi Kaffah (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2019)
Interpersonal intelligence is dynamic and not static, influenced by environment and culture. Intelligence is not genetic. Every child has the potential to improve their intelligence. Each intelligence has the potential to develop according to the environmental conditions. Based on this reason, living in a Pesantren environment consists of santri with heterogeneous backgrounds. The interactions are developed intensively between friends, seniors, teachers and kyai for twenty four hours, making boarding schools as an ideal place to develop interpersonal intelligence. In Pesantren they can learn to interact and understand the totality of diversity around it. This research is a qualitative research with a case study model. The object of this research is Pondok Pesantren Darul Huda Ponorogo. The purpose of this study to (1) to find out the concept of developing interpersonal intelligence Environmental Conditioning, Formation with understanding (insight) and Formation with role model, (2) to find out interpersonal intelligence development strategies which are; training to practice speech and listen effectively, giving a leadership role, giving discussion meetings and deliberations, telling the good characters, providing group support Internalization of the value of the kutub Turats in daily life, and 3) to find out a theory on the interpersonal intelligence development by stimulating interactive activities which have an impact on changes in individual attitudes. With interactive activity will create a good interpersonal communication and changing social attitudes.